The world has forgotten us : Sinjar and the Islamic State's genocide of the Yezidis - Schmidinger, Thomas, 1974- (Pluto Press, 2022)
"The persecution of the Yezidis, a religious community originating in Upper Mesopotamia, has been ongoing since at least the 10th century. On 3 August 2014, Islamic State attacked the Yezidi community in Sinjar, Kurdistan. Thousands were enslaved or killed in this genocide, and 100,000 people fled to Mount Sinjar, permanently exiled from their homes. Here, Thomas Schmidinger talks to the Yezidis in Iraq who tell the history of their people, why the genocide happened and how it affects their lives today. This is the first full account of these events, as told by the Yezidis in their own words, to be published in English. The failure of the Kurdistan Peshmerga of the PDK in Iraq to protect the Yezidis is explored, as is the crucial support given by the Syrian-Kurdish YPG. This multi-faceted and important history brings the fight and trauma of the Yezidis back into focus, calling for the world to remember their struggle."--